The Effect Of Transformational Leadership In Achieving High Performance Workforce That Exceeds Organisational Expectation: A Study From A Global And Islamic Perspective - Samir Ali Trmal; Ummi Salwa Ahmad Bustamam; Zainal Abidin Mohamed (Universal Publishers - Boca Raton, Florida, USA, 2024)
Over the last decade and a half, the study on transformational leadership in any organizational settings has gone through a significant evolution in terms of theory development as well as empirical investigations. Many researchers have now embarked on the study, both from the global perspective and from the Islamic perspective. Islam is the concept of leadership is interrelated to trust (amanah) which signifies a psychological contract between a leader and his followers whereby the leader will do his best to guide, protect and treat them fairly and with justice. As a result, our knowledge about this leadership style has deepened, and there are several dominant theories that are now established paradigms in the leadership field. Despite the development there is numerous magnitudes of these leadership forms that we still don’t know very much. Hence, it is only proper that we examine where we need to go into the future. Leaders play the primary role in establishing and motivating employees’ performance, but little research has examined the specific processes which stimulate the effect of transformational leadership resulting high-performance workforce exceeding organizational expectation. This study will seek the answer based on the global as well as the Islamic perspective.